Kinetics of Blood-Brain Barrier Transport of Monoclonal Antibodies Targeting the Insulin Receptor and the Transferrin Receptor - William M. Pardridge (MDPI AG, 2021)
Biologic drugs are large molecule pharmaceuticals that do not cross the blood-brain barrier (BBB), which is formed by the brain capillary endothelium. Biologics can be re-engineered for BBB transport as IgG fusion proteins, where the IgG domain is a monoclonal antibody (MAb) that targets an endogenous BBB transporter, such as the insulin receptor (IR) or transferrin receptor (TfR). The IR and TfR at the BBB transport the receptor-specific MAb in parallel with the transport of the endogenous ligand, insulin or transferrin. The kinetics of BBB transport of insulin or transferrin, or an IRMAb or TfRMAb, can be quantified with separate mathematical models. Mathematical models to estimate the half-time of receptor endocytosis, MAb or ligand exocytosis into brain extracellular space, or receptor recycling back to the endothelial luminal membrane were fit to the brain uptake of a TfRMAb or a IRMAb fusion protein in the Rhesus monkey. Model fits to the data also allow for estimates of the rates of association of the MAb in plasma with the IR or TfR that is embedded within the endothelial luminal membrane in vivo. The parameters generated from the model fits can be used to estimate the brain concentration profile of the MAb over time, and this brain exposure is shown to be a function of the rate of clearance of the antibody fusion protein from the plasma compartment.